Cut-off score of the Khalfa Hyperacusis Questionnaire with 10 selected items. (3rd March 2022) - Yamada, Hiroyuki; Ishikawa, Toru; Oishi, Naoki; Ogawa, Kaoru
Abstract: Objective: In the management of hyperacusis, the hyperacusis questionnaire (HQ) is a frequently used measure. It is comprised of 14 items, with a total score of 42 points. We have developed the Japanese version of the HQ, but the validity of the factors has not been considered. This study was performed to re-evaluate the HQ to confirm its validity and reliability. Design: Exploratory factor analysis was performed and we removed the problematic items with low factor loadings and re-evaluated the reliability and validity. Study Sample: Patients with hyperacusis (n = 109) were included. Hyperacusis was confirmed based on the patients' complaint of "intolerance to sound". Patients without hyperacusis but with tinnitus and/or hearing loss (n = 103) were also included. Results: Items 1, 5, 6, and 11 had low factor loadings; therefore, we removed these four items. The HQ with 10 items had high internal consistency reliability (Cronbach's α = 0.926). The mean total scores for the patients with and without hyperacusis were 16.3 and 4.0, respectively; the inter-group difference was statistically significant. We found the best score that maximised sensitivity and specificity was 8. Conclusions: The HQ with 10 items, up to 30 points and a cut-off score of 8 is appropriate for classifying hyperacusis.